2021
DOI: 10.3319/tao.2021.08.23.01
|View full text |Cite
|
Sign up to set email alerts
|

The determination of Thailand Geoid Model 2017 (TGM2017) from airborne and terrestrial gravimetry

Abstract: The Royal Thai Survey Department and Chiangmai University developed the Thailand geoid model 2017 (TGM2017) with a 1x1 grid to support the transformation between Global Navigation satellite System (GNSS) ellipsoid heights and Kolak-1915 vertical datum orthometric heights.TGM2007 was based on Thailand gravimetric geoid model 2017 (THAIG17) and 299 GNSS ellipsoidal heights co-located with Kolak-1915 heights. All terrestrial gravity data used for geoid computation came from the new national gravity network, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Similary, Australia has created its own geoid, known as the AUSGeoid, which is accurate to within 4-8 cm. Australian height datum (AHD) can be computed directly from the GNSS and AUSGeoid of accuracy of 6-13 cm (Intergovernmental Committee on Surveying and Mapping (ICSM), 2021) Additionally, Thailand's gravimetric geoid model 2017 (THAIG17) has rmse of 4.9 cm, which results in accurate heights of at least 10 cm accuracy level or better (Dumrongchai et al, 2021). However, the study used the geoid (geoid 2021) to extract the geoid undulation has reported accuracy of only about 8 cm in the sagarmatha region and 4 cm in the current study area.…”
Section: Precision Of Existing Geoidmentioning
confidence: 99%
“…Similary, Australia has created its own geoid, known as the AUSGeoid, which is accurate to within 4-8 cm. Australian height datum (AHD) can be computed directly from the GNSS and AUSGeoid of accuracy of 6-13 cm (Intergovernmental Committee on Surveying and Mapping (ICSM), 2021) Additionally, Thailand's gravimetric geoid model 2017 (THAIG17) has rmse of 4.9 cm, which results in accurate heights of at least 10 cm accuracy level or better (Dumrongchai et al, 2021). However, the study used the geoid (geoid 2021) to extract the geoid undulation has reported accuracy of only about 8 cm in the sagarmatha region and 4 cm in the current study area.…”
Section: Precision Of Existing Geoidmentioning
confidence: 99%